Graduate Management Admission Test Outcomes And The Academic Achievement: A Study On Masters Of Business Administration Students At Makerere University, Uganda - Wamala, Robert; Omala Kizito, Saint; Kakumba, Umar (American Journal of Business Education, 2012)
This study investigates whether the outcomes of the Graduate Management Admission Test (GMAT) can predict the academic achievement of enrollees in masters programs. The study is based on administrative data of 516 Masters of Business Administration (MBA) enrollees at the College of Business and Management Science, Makerere University in the 2011 and 2012 enrollment cohorts. The Cumulative Grade Point Average (CGPA) in the bachelor’s degree and that of the first year of master’s studies were adopted as measures of the academic achievement of enrollees. In the analysis, academic achievement of MBA enrollees was modeled using a robust regression by GMAT scores obtained during admission to the program and student characteristics—gender, other qualification, year of completion and outcome of the bachelor’s degree, and whether the candidate obtained his/her bachelor’s degree from Makerere University. In the results, a high GMAT score was significantly associated with high academic achievement among graduate students. This evidence suggests that the theory of an aptitude or admission test being a predictor of academic achievement of learners holds across disciplines. However, a significant association established in the results between the academic achievement of learners at the undergraduate and graduate stages indicates that the undergraduate achievement can be recommended as a cost free alternative for assessing the competence of candidates suitable for admission to the graduate program.
Keywords: Graduate Management Admission Test; Academic Achievement; Makerere University; Uganda